Novel cost-effective design for bio-volatilization studies in photosynthetic microalgae exposed to arsenic with emphasis on growth and glutathione modulation - Upadhyay, Atul K.; Mallick, Shekhar; Singh, Ranjan; Singh, Lav; Singh, Nitesh; Mandotra, S. K.; Singh, Arpit; Srivastava, Ravi Prakash; Pandey, Shivaraman; Saxena, Gauri (Frontiers in Microbiology, 2023)
A novel laboratory model was designed to study the arsenic (As) biotransformation potential of the microalgae Chlorella vulgaris and Nannochloropsis sp. and the cyanobacterium Anabaena doliolum. The Algae were treated under different concentrations of As(III) to check their growth, toxicity optimization, and volatilization potential. The results revealed that the alga Nannochloropsis sp. was better adopted in term of growth rate and biomass than C. vulgaris and A. doliolum. Algae grown under an As(III) environment can tolerate up to 200 μM As(III) with moderate toxicity impact. Further, the present study revealed the biotransformation capacity of the algae A. doliolum, Nannochloropsis sp., and Chlorella vulgaris. The microalga Nannochloropsis sp. volatilized a large maximum amount of As (4,393 ng), followed by C. vulgaris (4382.75 ng) and A. doliolum (2687.21 ng) after 21 days. The present study showed that As(III) stressed algae-conferred resistance and provided tolerance through high production of glutathione content and As-GSH chemistry inside cells. Thus, the biotransformation potential of algae may contribute to As reduction, biogeochemistry, and detoxification at a large scale.